Endodontic medicine: Interrelationships among apical periodontitis, systemic disorders, and tissue responses of dental materials - Cintra, Luciano Tavares Angelo [UNESP]; Estrela, Carlos; Azuma, Mariane Maffei; Queiroz, índia Olinta de Azevedo [UNESP]; Kawai, Toshihisa; Gomes-Filho, João Eduardo [UNESP] (FapUNIFESP (SciELO), 2018)
Endodontic medicine, which addresses the bidirectional relationship between endodontic infections and systemic diseases, has gained prominence in the field of endodontics. There is much evidence showing that while systemic disease may influence the pathogenesis of endodontic infection, endodontic infection can also cause systemic alterations. These alterations include more severe bone resorption and inflammation in the periapical area as well as enhanced systemic disease symptoms. Similarly, many reports have described the impact of systemic diseases on the tissue responses to dental materials. Conversely, the local use of dental materials may show systemic effects in the form of altered production of biomarkers. Thus, studies to better understand the mechanisms related to those connections are extremely important. In this context, the objective of this review was to analyze and discuss the current literature regarding the connections among these three factors-systemic diseases, endodontic infection, and endodontic dental materials-and determine how these connections may interfere in the systemic health status and the endodontic treatment outcomes, which are represented by periapical wound healing.
Keywords: Dental materials; Dental pulp necrosis; Endodontics; Metabolic diseases; Periapical periodontitis